Infrared transmittance spectra of polar stratospheric clouds. (January 2023) - Lecours, Michael; Bernath, Peter; Boone, Chris; Crouse, Jeff
Highlights: Remote sensing with Atmospheric Chemistry Experiment, ACE, satellite. Infrared solar transmittance spectroscopy with a Fourier transform spectrometer. Spectra and spectral modeling of polar stratospheric clouds, PSCs. Supercooled nitric acid found to be a common type of PSC. Abstract: Polar stratospheric clouds (PSCs) are responsible for polar ozone depletion. Infrared transmittance spectra of PSCs recorded by the Fourier transform spectrometer (FTS) on the Atmospheric Chemistry Experiment (ACE) satellite were used to determine the composition and properties of PSCs. These unique broad band infrared spectra identify PSCs as nitric acid trihydrate (NAT), supercooled ternary solutions (STS) of nitric and sulfuric acid, and ice, as expected. Quantitative modeling of these PSC spectra shows that supercooled nitric acid (SNA) is also common, i.e., "STS" with no observable sulfuric acid in their infrared spectra. ACE-FTS observations therefore classify PSCs into 4 basic spectral types, NAT, STS, SNA and ice, as well as their mixtures. As an example, this classification scheme was applied to the Antarctic for July to September 2019. The composition and particularly the phase of PSCs are critical to the understanding and detailed chemical modeling of polar stratospheric ozone depletion.